Man and culture: A philosophical anthology - Verene, Donald P. (New York Laurel, Dell publishing, 1970)
Explores the general outlines of the philosophy of culture by drawing together works by thinkers who either regard themselves as philosophers of culture or who would readily be so-called by other philosophers.